Hubungan Capacity Building terhadap Kinerja Karyawan Melalui Motivasi dan Kompetensi sebagai Variabel Intervening - Tauhid, Inna Hanifa; Rozikin, Mochammad (Jurnal Ilmiah Administrasi Publik, 2019)
Capacity building is a strategy to improve employee efficiency, effectiveness and performance. This study aims to determine the effect of capacity building on employee performance at the UB Head Office. Data collection techniques were using observation and questionnaires. Data analysis using Partial Least Square structural models with partial hypothesis testing. The population used was 798 employees at the Head Office of Universitas Brawijaya, with samples taken at three Bureaus which are: General and Civil Service Bureau, Academic and Student Affairs Bureau and the Finance Bureau. The results showed that there was a positive and significant influence on human resource building capacity, organizational strengthening and institutional reform on employee performance through competency and motivation of employees at the Central Office of Universitas Brawijaya.